Simulating a convectional heat transfer in buildings with radiant gas heating - Ermolaev Anton N.; Khaustova Olga V.; Turaev Ilya A. (MATEC Web of Conferences, 2018)
The paper presents the results of the simulation of convectional heat transfer in buildings with radiant gas heating. The study is provided by numerical researches based on existing buildings and numerical studies with the use of modern software ANSYS Multiphysics Fluent, Autodesk Inventor. The data reliability is ensured by the use of fundamental laws in regards to numerical researches and approved mathematic models application; certificated measuring equipment; licensed software products; matching of numerical and experimental researches; matching of the simulation with other works. The simulation of luminous infrared gas emitters of all thermal powers (5, 10, 15, 20, 30, 40 kW) in pre-wall and central placements at heights of 4, 5, 6, 7, 8, 9, 10 m was conducted. Gas-fired infrared heat emitters with heat output of 5, 10, 15, 20, 30, 40 kW were studied. Obtained function of IR-heated zone diameter is close to logarithmic function of thermal output. Effective emitter placement heights and least horizontal pitch for the given room volume were determined.